GE_GERICHTE PM/758/2018 vom 6. Dezember 2018 - GE Cour de justice (2018)
TRAITEMENT AMBULATOIRE ; MESURE THÉRAPEUTIQUE INSTITUTIONNELLE ; INTÉRÊT PUBLIC ; PROPORTIONNALITÉ | CP.59; CP.63; CP.63.al5.letb